Evaluation of the CALIPSO Lidar-observed particulate backscattering coefficient on different spatiotemporal matchup scales - Sun, Miao; Chen, Peng; Zhang, Zhenhua; Zhong, Chunyi; Xie, Congshuang; Pan, Delu (Frontiers in Marine Science, 2023)
The satellite lidar-derived ocean particulate backscattering coefficient (bbp) has rarely been validated globally with in situ observations, and we need to understand how well the satellite CALIPSO lidar bbp approach performs. Whether lidar bbp performs better in terms of observation accuracy compared to passive ocean color remote sensing has yet to be evaluated for detailed validation. With the continued deployment of the BGC-Argo float array in the global open ocean in recent years, data have accumulated with a total of 42,932 particulate backscattering coefficients (bbp) from 2010 to 2017, allowing for a finer spatial and temporal scale evaluation of the performance of the CALIPSO lidar-observed bbp. We evaluated the performance of CALIPSO-retrieved bbp products using the data detected by the BGC-Argo floats at 12 spatiotemporal matchup scales and discussed the differences in product performance at various interannual, seasonal, and spatial scales. We compare lidar, float, and ocean color bbp at the same locations and times and find that lidar bbp outperforms ocean color data. We also analyzed the key conversion factor β(π)/bbp at different spatial and temporal scales and found that there was a seasonal difference in the optimal conversion factor.